"Suojele unelmia, vaali toivoa" : nuorten suositukset lastensuojelun ja sijaishuollon laadun kehittämiseksi - Vario, Pipsa; Barkman, Johanna, 1965-; Kiili, Johanna; Nikkanen, Marko; Oranen, Mikko, 1961-; Tervo, Jaana, 1968- (Jyväskylä : Lapsiasiavaltuutetun toimisto, 2012)
"Skydda drömmarna, värna om hoppet" : rapport över en samrådsrunda med unga som är placerade i vård utom hemmet i anslutning till barnskyddet.
"Nurturing hopes, encouraging dreams" : a report on young people placed in alternative care under provisions for child welfare services, prepared on the basis of consultation with the young.
Keywords: Child Welfare -- trends; Child Advocacy -- legislation & jurisprudence; lapset (ikäryhmät); oikeudet; lapsen asema; lapsipolitiikka; lapsityö; hyvinvointi; lapsuus; lapsiasiavaltuutetut; perusoikeudet; lastensuojelu; sijaishuolto; laatu; kehittäminen; asiakkaat; nuoret; kokemukset; mielipiteet; selviytyminen; erfarenheter; kvalitet; barn (åldersgrupper); barndom; ungdomar; välfärd; rättigheter; barnets ställning; barnpolitik; barnverksamhet; barnombudsmän; barnskydd; vård i fosterhem; Suomi; Annual Reports